AN INVESTIGATION OF MOTIVATIONAL STRATEGIES USED BY ENGLISH TEACHERS IN TEACHING EFL IN SECONDARY ISLAMIC SCHOOLS IN TANGERANG - Fidaniar Tiarsiwi; Dini Amaniah (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2020)
The study aims to investigate the motivational strategies used by English teachers in teaching EFL in secondary Islamic schools in Tangerang and analysed it based on four motivational aspects as proposed by Zoltan Dornyei (2001). The focus question of the study was the way of motivational strategies used by English teachers in teaching EFL in secondary Islamic schools in Tangerang. The sub-focus questions of the study were the frequency of motivational strategies used by English teachers in teaching EFL in secondary Islamic schools in Tangerang and the implementation of motivational strategies that the English teachers used in teaching EFL in secondary Islamic schools in Tangerang. To answer the questions, the study employed a qualitative approach that applied a case study design through questionnaire, semi-structured interview and observation to collect the data. The participants of this study were twenty-five English teachers. Six English teachers were selected for individual interviews and classroom observations based on the resulted of the questionnaire which had been filled in by twenty-five English teachers. Those six interviewees were selected according to the result of the questionnaire. Two were from good category, other two interviewees were selected as the moderate, while the other two were from poor category.